Neurobiological developmental disorders in preschool girls are associated with obesity - van Veen, Wilma J.; Burger, Michiel; van Vliet, Michel J. (International Journal of Contemporary Pediatrics, 2024)
Background: The prevalence of abnormal weight in young children with neurobiological developmental disorders is not known. Children with abnormal weight are at risk for both mental health problems now and in their future. Moreover, abnormal weight can have a detrimental effect on their treatment. This prospective study examines the length and weight in preschool children with neurobiological developmental disorders requiring special day care. Methods: Trained medical employees measured height and weight of children aged 3 till 5 years old with developmental disorders, who started special youth day care between 2019 and 2021 in the province of Drenthe in the Netherlands. Results: A total 73% of the children had normal weight, 16% had overweight, 12% were underweight. Girls had more often overweight (28%) and underweight (14%), compared to boys. Conclusions: Our results suggest that pre-school children and especially girls with psychological problems, have already a significant increased risk of an abnormal body mass index (BMI). Although studies with a larger study population are needed to ascertain this conclusion, screening for an abnormal BMI should be conducted as a standard procedure in this group of children, since it can affect their therapy and future health.